Study of the Harmful Impact of the Environment on the Health of the Population of the Chemical Industrial Enterprise "Maksam-Chirchik" of the Tashkent Region - Mirziyatovna, Mirsharipova Zilola; Odilovna, Nizamova Dilrabo; Mirzabekovna, Turabekova Urkhia (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents the results of a sociological study concerning the incidence and awareness of residents of the city of Chirchik (Tashkent region) about the health risks of environmental pollution by waste from the chemical industrial enterprise "Maxam-Chirchik". Among the environmental problems, the respondents noted, first of all, pollution of atmospheric air, water, unsanitary state of the territory, harmful chemicals in food and problems of obtaining information about the ecology of the region, as well as an increase in the incidence of respiratory diseases. In general, the opinion of the population of the city of Chirchik corresponds to the real state of the environment